2011
DOI: 10.1016/j.vetimm.2011.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Features of follicular dendritic cells in ovine pharyngeal tonsil: An in vivo and in vitro study in the context of scrapie pathogenesis

Abstract: a b s t r a c tAlthough the alimentary tract has been suggested as the most likely portal of entry in natural scrapie, a growing amount of data indicates that the respiratory system and more specifically the pharyngeal tonsils serve as a natural portal of entry for scrapie.This study describes for the first time the broad cell populations in the lymphoid compartment of pharyngeal tonsils and more specifically inside the lymphoid follicles where the scrapie agent accumulates during the period of latency.Follicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
4
4
0
Order By: Relevance
“…This is in accordance with the descriptions given by Casteleyn et al, (2011) and Toppets et al, (2011) in sheep.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…This is in accordance with the descriptions given by Casteleyn et al, (2011) and Toppets et al, (2011) in sheep.…”
Section: Resultssupporting
confidence: 94%
“…This was characterized by decreased height of the epithelial cells, absence of cilia and goblet cells and heavy infiltration of lymphocytes through the interrupted basement membrane. These observations are in accordance with the findings of Kumar and Timoney (2001) Toppets et al, (2011) suggested that the pharyngeal tonsils were perfectly adapted to sample foreign antigens due the massive intraepithelial lymphocyte infiltration. The lymphoepithelial barrier sampled and transferred antigens to the underlying lymphoid tissue (Perry and Whyte, 1998).…”
Section: Resultssupporting
confidence: 93%
“…Kumar et al () earlier demonstrated a rich population of B‐cells in the central follicular area, whereas the dome and parafollicular areas contained both CD4+ and CD8+ lymphocytes in the nasopharyngeal tonsil of the horse. Furthermore, FDCs, and stromal cells located in the light zone of the germinal centre of the lymphoid follicle, have been implicated in the pathogenesis of transmissible spongiform encephalopathy disease in sheep (Toppets et al, ). The location of these nodules and the topography of the associated FAE have been the basis of the suggestion that they act as mechanisms for trapping and sampling antigens in the airstream (Mair, Batten, Stokes, & Bourne, ).…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, bioassays that use non-living material, including highly sensitive versions with transgenic mice, are inherently limited as to the information they can provide on infectivity of the scrapie agent. The scrapie agent can be found in the lymphoreticular system of both sheep (van Keulen et al, 1996;Schreuder et al, 1998;Andreoletti et al, 2000;O'Rourke et al, 2000O'Rourke et al, , 2002Press et al, 2004;Dennis et al, 2009;Ryder et al, 2009;Jeffrey et al, 2011;Toppets et al, 2011), and goats (Monleon et al, 2001;Gonzalez et al, 2009Gonzalez et al, , 2010.…”
Section: Studies Bymentioning
confidence: 99%
“…(3) The milk of infected sheep and infected goats (Konold et al, 2013a(Konold et al, , 2013b can carry the scrapie agent. (4) The lymphoreticular system of infected sheep (van Keulen et al, 1996;Schreuder et al, 1998;Andreoletti et al, 2000;O'Rourke et al, 2000O'Rourke et al, , 2002Dennis et al, 2009;Ryder et al, 2009;Toppets et al, 2011), and infected goats (Gonzalez et al, , 2010Monleon et al, 2011). In both sheep and goats, the scrapie agent is present in cells of the lymphocyte lineage (T cell and B cells) and the mononuclear phagocyte lineage (macrophages and dendritic cells) and in discrete and diffuse lymphoid organs, where it is used to diagnose scrapie during the preclinical stage of infection.…”
Section: Extension Of Findings To Goatsmentioning
confidence: 99%